In-company project: la banque postale, bordeaux Implementation of an organizational change and its impact on managers’ role - Commeny, Justine Margaux (2016)
While organizations are increasingly confronted with problems of changes, the success rate of implementation is still relatively low. Organizational change is a real challenge for a company; sometimes, managers have to deal with resistance to change from individuals and employees, especially in some sectors such as the industry or public sector. By their particular position in the organization, proximity managers have a strong impact on the success or failure of organizational changes. However, the literature on organizational changes doesn’t really study this population. The proximity managers are often presented as "agents of change", that is to say, ensuring the implementation and prescription of change imposed by top management. This paper aims to understand the role of proximity managers during an organizational change, and the evolution of their role regarding the change. To do so, we did a qualitative study within a French company who faced several changes during the last five years. Our research is based on non-participants observations and on semi-structured interviews.